Comparison of the Posterior and Paraspinal Approaches for the Treatment of Thoracolumbar Burst Fractures: A Randomized Controlled Trial - Pisuitthanakan, MD, Satapong (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: Burst fractures cause over half of all thoracolumbar fractures, for which the posterior approach has been considered the standard approach. The paraspinal approach has proven safe and effective for thoracolumbar injury. This study aimed to compare the clinical and radiographic outcomes between the two approaches. Methods: This randomized controlled trial included 24 patients with isolated thoracolumbar burst fractures between July 2016 and August 2018. Patients were categorized into two groups: paraspinal and posterior approaches. The primary outcome was postoperative pain on days 1, 2, 3, and 14. The corrected Cobb’s angle; operation time; intraoperative blood loss; opioid usage on days 1, 2, and 3; Oswestry Disability Index (ODI, Thai version); and percentage reduction loss at 3 months were secondary outcomes. Participants were assessed on post-intervention days 1, 2, 3, 14, and 90. Results: The mean visual-analog-scale (VAS) scores on postoperative days 1, 2, 3, and 14 (8.6 ± 0.8, 7.1 ± 0.6, 5.5 ± 1.3, 5.5 ± 0.8); intraoperative blood loss (395.8 ± 113.7 mL); opioid usage on days 2 and 3 (13 ± 1.5 mg, 8.3 ± 1.9 mg); and postoperative ODI (23.5 ± 3.5) were significantly lower (P<0.05) in the paraspinal-approach group than in the posterior-approach group (mean VAS on postoperative days 1, 2, 3, and 14 [9.2 ± 0.5, 8.3 ± 0.3, 7.5 ± 0.8, 6.7 ± 0.5]; intraoperative blood loss [590 ± 70.1 mL]; opioid usage on days 2 and 3 [15.8 ± 1.9 mg, 11.7 ± 1.6 mg]; and postoperative ODI [40 ± 4.2]). There was no statistical differences in operative time, corrected Cobb’s angle, and percentage reduction loss. Conclusions: The paraspinal approach is significantly advantageous over the conventional posterior approach regarding postoperative pain, intraoperative blood loss, opioid usage, and ODI at 3 months, thus corroborating the minimally invasive concept.